DEGRADATION OFSODIUMALGINATE BYLOWENERGYELECTRON BEAM - Tita Puspitasari; Naotsugu Nagasawa; Toshiaki Yagi; Fumio Yoshii (Jurnal Sains Materi Indonesia, 2006)
DEGRADATION OFSODIUMALGINATE BYLOWENERGYELECTRON BEAM. High viscosity (HV) and low viscosity (LV) alginate prepared in 5% solutions were irradiated by low energy electron beam (LEEB) at 55oC and ambient temperature respectively. Oligoalginates with molecular weight lower than 20,000 Da and broad molecular weight distribution were obtained until 60 minutes of irradiation. The decrease in molecular weight was accompanied by appearance of UV absorbance peak at 265 nm. LV alginate was preferable to use as raw material for LEEB irradiation process than HV alginate.